MEDIA AUDIOVISUAL TENTANG FARDHU ‘AIN (SUBUH, ZUHUR, ‘ASAR, MAGHRIB, DAN ISYA) PADA PELAJARAN FIQIH SISWA KELAS VI MADRASAH IBTIDAIYAH NEGERI 7 LANGKAT BOHOROK - Muhijar Muhijar (Universitas Negeri Medan, 2020)
Audiovisual media about Fardhu 'Ain (Fajr, Zuhur,' Asar, Maghrib, and Isya) can improve the results of Islamic Fiqh Lessons for Class VI Madrasah Ibtidaiyah Negeri 7 Langkat Bohorok, this can be seen from the calculation results in the first cycle between the first prayer practice test scores. with the second prayer practice test value obtained Product Correlation Moment r count of 0.780 and the t test value of 6.20, and in the second cycle between the third prayer practice test value and the fourth prayer practice test value obtained Product Correlation Moment r count 0.870 and test value t of 8.72. Audiovisual Media About Fardhu 'Ain (Fajr, Zuhur,' Asar, Maghrib, and Isya) can increase the activities of Class VI Students at Madrasah Ibtidaiyah Negeri 7 Langkat Bohorok, this can be seen from the presence of students before the classroom research action is done by 85%, the first cycle The presence of students after the classroom research action was 90%, the first cycle of student attendance after the classroom research action was 95%, the second cycle the attendance of students after the classroom research action was 100%.Keywords: Audiovisual Media About Fardhu 'Ain (Fajr, Zuhur,' Asar, Maghrib, and Isha)